Superconducting gap anisotropy sensitive to nematic domains in FeSe - Takahiro Hashimoto (Nature Portfolio, 2018)
The superconducting gap structure of FeSe remains a debated issue. Here, Hashimoto et al. report momentum dependence of the gap in single- and multi-domain regions of orthorhombic FeSe crystals, revealing an unusual node lifting of the gap structure in multi-domain regions.